Case of uterine rupture after multiple intrauterine operations and uterine artery embolization. Issue 3 (3rd December 2018) - Ando, Miho; Goto, Maki; Matsuoka, Sakiko; To, Yoko; Eguchi, Fuyuki; Tsujioka, Hiroshi
Abstract: Uterine rupture is rare but may result in both maternal and fetal death. The factors involved in such deaths depend on each case, but uterine artery embolization (UAE), the common treatment for hemorrhage, is possibly one factor. UAE may be related to uterine rupture or placenta accreta, but few data exist regarding UAE and uterine rupture. Here, we present a case of uterine rupture associated with placenta accreta that occurred after UAE. The case is a 35‐year‐old woman who became pregnant after undergoing UAE because of treatment for placental polyps twice. She underwent emergency cesarean delivery for uterine rupture. At the same time, she underwent hysterectomy because of placenta accreta. The uterus ruptured at the location where the polyp had emerged previously. Therefore, we present a case where UAE, uterine rupture and placenta accreta are possibly associated, and highlight the need for caution when performing UAE multiple times.